2017
DOI: 10.1159/000484144
|View full text |Cite
|
Sign up to set email alerts
|

Significance of MRI/Transrectal Ultrasound Fusion Three-Dimensional Model-Guided, Targeted Biopsy Based on Transrectal Ultrasound-Guided Systematic Biopsy in Prostate Cancer Detection: A Systematic Review and Meta-Analysis

Abstract: Purpose: To assess MRI/Transrectal Ultrasound (TRUS) fusion three-dimensional model-guided targeted biopsy (3D-Tb) versus TRUS-guided systematic biopsy (Sb) in detecting overall and high-Gleason-score (≥7) prostate cancer (PCa). Methods: Pubmed and Web of science were searched. Studies with men having a suspicious lesion on MRI were included, which were divided into initial biopsy, previous negative biopsy, and mixed groups in meta-analysis. Results: Totally 13 cohorts in 12 studies, with 3,225 men were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
2
7
0
1
Order By: Relevance
“…Similar findings were reported by Tang et al. on high-risk PCa detection, however, meta-analysis mainly evaluated MRI/TRUS fusion 3D model-guided targeted biopsy for PCa ( 44 ). Patients with high-risk prostate cancer are at an increased risk of biochemical recurrence, metastatic progression and cancer-related death following primary treatment compared with patients with low-risk or intermediate-risk disease ( 45 ).…”
Section: Discussionsupporting
confidence: 78%
“…Similar findings were reported by Tang et al. on high-risk PCa detection, however, meta-analysis mainly evaluated MRI/TRUS fusion 3D model-guided targeted biopsy for PCa ( 44 ). Patients with high-risk prostate cancer are at an increased risk of biochemical recurrence, metastatic progression and cancer-related death following primary treatment compared with patients with low-risk or intermediate-risk disease ( 45 ).…”
Section: Discussionsupporting
confidence: 78%
“…Choosing MRI examination before prostate biopsy not only has advantages of the highly sensitivity for detecting PCa, but may also show the location of the lesion (33,34). However, as a new monitoring tool, it might require PCa-suspected patients to bear more financial burdens.…”
Section: Discussionmentioning
confidence: 99%
“…31 A previous meta-analysis indicated that MRI-guided targeted biopsy improved the CDR among males with a clinical suspicion of prostate cancer along with previous negative biopsy results. 32 Optimistically, MRI may offer superior anatomic details and have the ability to access cellular density based on water diffusion and blood flow (based on contrast enhancement). Currently, the most common protocols include biparametric prostate MRI (bpMRI) and multiparametric MRI (mpMRI).…”
Section: Discussionmentioning
confidence: 99%